Insect Pests of Grapes in Florida - Oscar Liburd; Gisette Seferina; Scott Weihman (EDIS)
Florida has approximately 1,500 acres of grapes. With increased funding from the Viticulture Advisory Council (VAC) to establish new wineries throughout the state, production is expanding rapidly. Muscadine grapes, Vitis rotundifolia Michx are the principal type of grapes cultivated in Florida. Only a few acres (< 200) of bunch grapes, Euvitis spp., are grown in Florida. In general, grapes are susceptible to many insect pests. Some of the common insect pests attacking grapes in Florida include: grape root borer, glassy-winged sharpshooter, grape flea beetle, grapevine aphid, grape leaffolder, grape curculio, and grape phylloxera. This document is Fact Sheet ENY-713, a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2004.